Having a Look on the History of Irony - E’tibor Bahriddinova (Zien Journals, 2022)
In this article is about the theoretical views connected with the characterizing emergence of cynical, expressive words. Besides, some comments are also made about ironically related situations and types, approaches to its application.
Keywords: irony; approach; situation; handling